2023
DOI: 10.1371/journal.pone.0292159
|View full text |Cite
|
Sign up to set email alerts
|

Trends and influence factors in the prevalence, awareness, treatment, and control of hypertension among US adults from 1999 to 2018

Zhixing Fan,
Chaojun Yang,
Jing Zhang
et al.

Abstract: Objective We aimed to describe the trends and influence factors in the prevalence, awareness, treatment, and control of hypertension among US Adults from 1999 to 2018. Methods We utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning ten survey cycles (n = 53,496). Prevalence, awareness, treatment, and control of hypertension were calculated using survey weights. Joinpoint regression and survey-weighted generalized linear models were used to analyze trends and influence fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…The present study adds to the literature by showing that decreasing trends in the diagnosis of hypertension persisted in the last years despite the human crisis related to the COVID-19 pandemic. Finally, it should also be noted that other studies have found either stable ( 10 , 11 , 14 ) or increasing trends in the prevalence of hypertension ( 9 , 15 , 16 , 18 ). This discrepancy in the findings in the literature may be related to several factors, such as differences in the settings in which the studies of interest were conducted, differences in the years during which the data were collected, and differences in the definition of hypertension.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The present study adds to the literature by showing that decreasing trends in the diagnosis of hypertension persisted in the last years despite the human crisis related to the COVID-19 pandemic. Finally, it should also be noted that other studies have found either stable ( 10 , 11 , 14 ) or increasing trends in the prevalence of hypertension ( 9 , 15 , 16 , 18 ). This discrepancy in the findings in the literature may be related to several factors, such as differences in the settings in which the studies of interest were conducted, differences in the years during which the data were collected, and differences in the definition of hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…It should be noted that this study apart, little research has analyzed trends in the prescription of antihypertensive drugs. A survey of 53,496 adults living in the USA found that, among those with hypertension, there was an uptrend in the use of ACEis and ARBs and a downtrend in the use of BBs between 1999 and 2018 ( 18 ). Regarding CCBs, there was an increase in the use of these molecules until 2005 and a subsequent decrease after 2005.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations